2023
DOI: 10.1002/est2.445
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the electrochemical capacitance of carbon nanosheets by optimizing its thickness through controlling the carbon precursor in salt‐template

Abstract: Herein, two‐dimensional (2D) carbon nanosheets derived from biomass precursor is successfully synthesized via a cost‐effective salt‐templated process. Microstructural characterization and Raman spectral analysis of the sample derived from the salt template method reveals the formation of carbon nanosheets. The nanosheet thickness and its capacitance have been altered by varying the carbon precursor to salt‐template ratio. From the AFM data, the thickness of the as‐prepared thin carbon sheet was measured as ~5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…For coin cell fabrication, Ni foam coated with electrode material (~6 mg) and 1 M Na 2 SO 4 (electrolyte) was used. The process adopted for the fabrication of coin cells has been described in our earlier paper 25 . The CV and GCD measurements of coin cells were performed for the potential window from 0 to 1.4 V and the electrochemical impedance spectrum was measured from 20 kHz to 100 mHz.…”
Section: Methodsmentioning
confidence: 99%
“…For coin cell fabrication, Ni foam coated with electrode material (~6 mg) and 1 M Na 2 SO 4 (electrolyte) was used. The process adopted for the fabrication of coin cells has been described in our earlier paper 25 . The CV and GCD measurements of coin cells were performed for the potential window from 0 to 1.4 V and the electrochemical impedance spectrum was measured from 20 kHz to 100 mHz.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the symmetric supercapacitor device assembled using thinner carbon nanosheets had a capacitance of 70.1 F g −1 with energy and power densities of 9.7 W h kg −1 and 20 kW kg −1 , respectively. 179 Pramanik et al presented the synthesis of a composite comprising nanoscale discrete Mn 3 O 4 particles (20 nm) into a two-dimensional sheet-like N-incorporated mesoporous carbon using NaCl crystallites as an exo-template, which demonstrated excellent performance as anode for a lithium ion battery. 180…”
Section: The Roles Of Salt In Carbon Synthesismentioning
confidence: 99%
“…This suggests that SCGs would be an ideal candidate for solid waste cycling. In addition, it has been reported that after carbonization and activation, SCGs can generate high-value two-dimensional (2D) porous carbon nanosheets (PCNs) The interlinked hierarchical porous structure of the 2D PCNs, combined with the 2D framework and pore architectures, has a high specific surface area and porous channels, as well as good electrical conductivity, resulting in superior potential in energy-storage applications, especially in supercapacitors, ,, lithium–sulfur batteries, and metal–air batteries. …”
Section: Introductionmentioning
confidence: 99%